Maternal Anxiety Symptoms and Self-Regulation Capacity Are Associated With the Unpredictability of Maternal Sensory Signals in Caregiving Behavior - Holmberg, Eeva; Teppola, Taija; Pajulo, Marjukka; Davis, Elysia Poggi; Nolvi, Saara; Kataja, Eeva-Leena; Sinervä, Eija; Karlsson, Linnea; Karlsson, Hasse; Korja, Riikka (Frontiers in Psychology, 2020)
The unpredictability of maternal sensory signals in caregiving behavior has been recently found to be linked with infant neurodevelopment. The research area is new, and very little is yet known, how maternal anxiety and depressive symptoms and specific parental characteristics relate to the unpredictable maternal care. The aims of the current study were to explore how pre- and postnatal maternal anxiety and depressive symptoms and self-regulation capacity associate with the unpredictability of maternal sensory signals. The study population consisted of 177 mother-infant dyads. The unpredictability of the maternal sensory signals was explored from the video-recorded mother-infant free play situation when the infant was 8 months of age. Pre- and postnatal anxiety and depressive symptoms were measured by questionnaires prenatally at gwks 14, 24, 34 and 3 and 6 months postpartum. Maternal self-regulation capacity, a trait considered to be stable in adulthood, was assessed using adult temperament questionnaire when the infant was 12 months of age. We found that elevated prenatal maternal anxiety symptoms associated with higher unpredictability in the maternal care while depressive symptoms were unrelated to the unpredictability of maternal care. Moreover, the association was moderated by maternal self-regulation capacity, as higher anxiety symptoms during pre-and postnatal period were associated more unpredictability among the mothers with low self-regulation capacity. The combination of higher amount of maternal anxiety symptoms and lower self-regulation capacity seems to constitute specific risk for the unpredictable maternal care.